Bit error rate analysis model of M-APSK based on total probability formula - HUAN Hao; REN Kexue (Tongxin xuebao)
To efficiently evaluate the performance of M-APSK modulation scheme over an additive white Gaussian noise channel, a theoretical bit error rate analysis model was proposed based on total probability formula. Firstly, the constellation plane was divided into regions according to the distribution of constellation points and their encoding characteristics. Then, the probability expression of the decision error of each bit was derived from the probability of the received symbol falling in the corresponding region. Finally, the exact closed-form solution of theoretical bit error rate was obtained. Taking 16APSK and 32APSK as examples, the theoretical bit error rate formula of all kinds of constellations was derived, which was in excellent agreement with Monte Carlo simulation. This model is universal, PSK, QAM, PAM, APSK and other modulation methods can use this model to obtain the exact closed-form solution of theoretical bit error rate. Compared with the complex two-dimensional probability integral method which relies on a large number of numerical calculations, the proposed model can give the bit error rate performance of M-APSK more conveniently.